1994
DOI: 10.1007/bf02375688
|View full text |Cite
|
Sign up to set email alerts
|

Sequential treatment of osteopenic ovariectomized rats with parathyroid hormone (1-34) fragment and pamidronate

Abstract: Abstract:Low doses of PTH(1-34) stimulate bone formation in rats but the effect is reversed after PTH withdrawal. This study shows that this reversal is prevented when sequential PTH-APD treatment is employed. Seventy 3-month-old female wistar rats were ovariectomized, and fed with regular rodent chow and water ad libitum. Twelve weeks later they were divided into seven groups and treated as follows: GI: 3w PTH (5d/w, 20ttg/kg/d sc). G2: 3w saline (5d/w, sc). G3: lw ADP (5d/w, 250 #g/kg/d sc) -~ 3w PTH. G4: lw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…N-terminal portion of PTH(1-34) has been shown to be able to be applied to the treatment of osteoporosis. Cheng [29] showed that PTH preparation stimulated bone formation in ovariectomized rats and thereversed process was counteracted by administration of pamidronate, stressing the significance of combination of PTH-pamidronate in the treatment of osteoporosis. C-terminal PTH was studied by some groups in Japan.…”
Section: Biological Activity Of Pth Fragmentsmentioning
confidence: 98%
“…N-terminal portion of PTH(1-34) has been shown to be able to be applied to the treatment of osteoporosis. Cheng [29] showed that PTH preparation stimulated bone formation in ovariectomized rats and thereversed process was counteracted by administration of pamidronate, stressing the significance of combination of PTH-pamidronate in the treatment of osteoporosis. C-terminal PTH was studied by some groups in Japan.…”
Section: Biological Activity Of Pth Fragmentsmentioning
confidence: 98%